Eksplorasi Pengaruh Pandemi COVID-19 Terhadap Diagnostic Delay Dan Treatment Delay Pada Pasien Kanker Payudara - Melian, Ruella Rivenska; Rafli, Rhandyka; Maribeth, Annisa Lidra (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
The COVID-19 pandemic has had an impact on health services for breast cancer patients. During the COVID-19 pandemic, there were new government regulations, namely PSBB or large-scale social restrictions. During the PSBB, activities in public facilities are limited to only urgent interests. Therefore, breast cancer patients have difficulties during examination and treatment during the COVID-19 pandemic. The obstacles for breast cancer patients are difficulties in mobilizing to the hospital, health protocol regulations such as maintaining distance, discomfort when wearing masks and swabs before treatment, the emergence of fear and anxiety, expensive transportation costs during examination and treatment, and psychological disorders. So the impact is delay in examination (diagnostic delay) and delay in treatment (treatment delay) of breast cancer patients. This study uses a qualitative descriptive method with an in-depth interview approach that is guided by semi-structured questions and triangulates the perspectives of patients, patients' families, and health workers. The study was conducted from November 2021 to August 2022. The sample used was 27 respondents by purposive sampling. Analysis using condensed text system. There are breast cancer patients who express fear of seeking treatment during the COVID-19 pandemic because of the increasing number of pandemic cases and the stigma of being "covided". However, there are patients who express that they are not afraid to seek treatment during the pandemic because they have an optimistic and strong faith. Patients have problems seeking treatment during the pandemic due swab before treatment, feeling uncomfortable when wearing a mask, and transportation costs constraints. Patients experience diagnostic and treatment delays during the pandemic due to fear of being infected with the corona virus, lack of knowledge about symptoms and treatment of breast cancer, belief in alternative medicine, shyness to carry out initial examinations, fear of medical action, and queue lists. Based on the results of the study, it can be concluded that there are internal and external factors that influence the COVID-19 pandemic on diagnostic delay and treatment delay in breast cancer patients